Southern Tapanuli Society Perception of Pulmonary TB Health and Diseases - Fahmi, Ismail; Badaruddin, Badaruddin; Rochadi, R. Kintoko; Lubis, Rahayu (Budapest International Research in Exact Sciences (BirEx) Journal, 2019)
Community empowerment programs to tackle pulmonary TB have never been implemented in South Tapanuli Regency, North Sumatra Province, Indonesia. Difficulties in designing interventions related to the socio-cultural community are one of the reasons. This study aims to understand people's perceptions of pulmonary TB health and disease and understand how the community prevents pulmonary TB. Qualitative research was carried out through focus group discussions and in-depth interviews. Participants were chosen purposively based on socioeconomic status, community / religious / adat leaders, and community health center officials, and government health officials. Data were analyzed using content analysis. The results of the analysis summarize the eight categories of statements that most often appear, namely: (1) Pulmonary TB is a dangerous disease; (2) the causes of pulmonary TB disease; (3) stigma related to pulmonary TB; (4) pulmonary TB treatment; (5) prevention of pulmonary TB; (6) information sources; (7) the role of community / religious / adat leaders; and (8) community action patterns. These eight categories are grouped into three domain structures, namely: (1) people's perception of pulmonary TB disease; (2) how to prevent pulmonary TB; and (3) health promotion strategies. The theme of deliberation, consensus, cooperation, and harmony that is identical to Dalihan Na Tolu's philosophy emerged as the perception of the people of South Tapanuli towards pulmonary TB disease.